2007
DOI: 10.1007/s10969-007-9032-5
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale, semi-automated purification of eukaryotic proteins for structure determination

Abstract: A simple approach that allows cost-effective automated purification of recombinant proteins in levels sufficient for functional characterization or structural studies is described. Studies with four human stem cell proteins, an engineered version of green fluorescent protein, and other proteins are included. The method combines an expression vector (pVP62K) that provides in vivo cleavage of an initial fusion protein, a factorial designed auto-induction medium that improves the performance of small-scale produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
(68 reference statements)
0
18
0
Order By: Relevance
“…Based on observed expression levels, other applications might also be supported by small-scale autoinduction experiments. For example, cultures obtained from autoinduction can yield sufficient purified protein for automated protein purification (Frederick et al, 2007), microfluidics-based crystallization screening (van der Woerd et al, 2003; Segelke, 2005), initial nanoliter-scale crystallization trials (Lion et al, 2004; Zheng et al, 2005), 15 N HSQC NMR measurements (Kennedy et al, 2002; Galvao-Botton et al, 2003), or functional and enzymatic characterizations (Kumar and Clark, 2006; Blommel and Fox, 2007). …”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on observed expression levels, other applications might also be supported by small-scale autoinduction experiments. For example, cultures obtained from autoinduction can yield sufficient purified protein for automated protein purification (Frederick et al, 2007), microfluidics-based crystallization screening (van der Woerd et al, 2003; Segelke, 2005), initial nanoliter-scale crystallization trials (Lion et al, 2004; Zheng et al, 2005), 15 N HSQC NMR measurements (Kennedy et al, 2002; Galvao-Botton et al, 2003), or functional and enzymatic characterizations (Kumar and Clark, 2006; Blommel and Fox, 2007). …”
Section: Commentarymentioning
confidence: 99%
“…Work from the authors’ laboratory has shown autoinduction is effective in 2-liter shaken bottles, 96-well growth blocks, and automated stirred-vessel fermenters (Blommel and Fox, 2007; Frederick et al, 2007). The different autoinduction results presented here include the use of shaken bottles (Fig.…”
Section: Commentarymentioning
confidence: 99%
“…The E. coli strain B834-pRARE2, which is useful in SeMet labeling for phase determination in X-ray crystallography, was the expression host [16]. Small-scale trials evaluating expression, solubility, and tag cleavage were carried out using autoinduction in both chemically defined and complex medium [5].…”
Section: Target Genesmentioning
confidence: 99%
“…For a life science lab wishing to automate the purification of biomolecules such as protein and nucleic acids, there are several relatively inexpensive systems available: Promega's Maxwell 16 (16 samples) and Thermofisher’s Kingfisher (24 samples) which both use paramagnetic particle technology for protein and nucleic acid purification [6, 7], the Bio-Rad Profinia (1 sample) that can run 2 sequential columns (i.e. affinity followed by desalting) for protein purification [8] and Qiagen’s QIAcube (12 samples) for protein and nucleic acid purification [9].…”
Section: Introductionmentioning
confidence: 99%